DINAMIKA LITERASI INFORMASI POLITIK DI KALANGAN AKTIVIS MAHASISWA ISLAM - Testiani Makmur; Dafrizal Samsudin (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2022)
This study aims to determine the profile of student political literacy among student organizations PMII, HMI and KAMMI at UIN Sulthan Thaha Jambi. A qualitative approach with semi-structured interviews, observations and literature studies was carried out to obtain informant data from each student organization consisting of the General Chair, Deputy Chair of the advocacy section, Secretary General, Action Coordinator.This study shows that being an Islamic student activist is driven by personal internal factors such as a sense of conformity with the ideology and spirit of Islamic da'wah, personal self-awareness and a critical attitude. External factors such as the influence of seniors and a positive image of student organizations. Sources of student political information are conventional media, new media such as websites and social media, discussion forums and experts. The search for political information is driven by the need for political information, leadership spirit, political awareness and interest in understanding the good/bad world of politics. Evaluation of each political information is carried out by comparison of sources and discussion. Political information is useful for students to meet the information needs and discussion material of their peers. Synergy between students, higher education institutions and student organizations is an important factor in increasing political information literacy among students.